Below the 12-vertex: 10-vertex carborane anions as non-corrosive, halide free, electrolytes for rechargeable Mg batteries. Issue 32 (6th April 2017) - McArthur, Scott G.; Jay, Rahul; Geng, Linxiao; Guo, Juchen; Lavallo, Vincent
Abstract : The synthesis and application of the first high voltage, non-corrosive, Mg battery electrolyte based on small carborane anions are reported. This electrolyte displays equal oxidative stability compared to its larger 12-vertex cousin, but is more cost effective to prepare. Abstract : The development of practical Mg based batteries is limited by the lack of a library of suitable electrolytes. Recently a 12-vertex closo -carborane anion based electrolyte has been shown to be the first electrolyte for Mg based batteries, which is both non-corrosive and has high electrochemical stability (+3.5 V vs. Mg 0/2+ ). Herein we show that smaller 10-vertex closo -carborane anions also enable electrolytes for Mg batteries. Reduction of the trimethylammonium cation of [HNMe3 1+ ][HCB9 H9 1− ] with elemental Mg yields the novel magnesium electrolyte [Mg 2+ ][HCB9 H9 1− ]2 . The electrolyte displays excellent electrochemical stability, is non-nucleophilic, reversibly deposits and strips Mg, and is halide free. This discovery paves the way for the development of libraries of Mg electrolytes based on more cost effective 10-vertex closo -carborane anions.